EKSISTENSI AMMALANGNGANG TOBANG DALAM PERNIKAHAN PERSPEKTIF HUKUM ISLAM ( STUDI KASUS DESA LANGKURA KECAMATAN TURATEA KABUPATEN JENEPONTO - Tanri, Justamin; Asni; Siti Nurul Fatimah (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract This study discusses the Existence of Ammalanngang Tobang in Islamic Law Perspective Marriage. The author examines how the existence of Ammalangkang Tobang in marriage in the perspective of Islamic law. This research is a fieldresearch that describes the results of the discussion through a descriptive qualitative method, using a normative theological approach. Primary data was obtained directly through interviews, while secondary data was obtained through documentation, literature and book literature. Data analysis used reduction, presentation, comparison and conclusion techniques. The results of this study reveal that the people of Jeneponto Regency, especially Langkura Village, still maintain the Ammalanggang Tobang tradition in marriage, Ammalanggang Tobang is the process of handing over gifts in the form of the groom's household furniture to the bride after the wedding. Conceptually, traditional Islamic law is included in Al-Urf or repeated habits. In its own application, the Ammalangngang Tobang tradition in marriage is legally valid in Islam because it does not contain elements of associating partners with Allah and does not conflict with the texts of the Koran and hadith. Keywords: Islamic Law, Ammalangngang Tobang, Marriage.